Corporate Social Responsibility, Employee Organizational Identification, and Creative Effort: The Moderating Impact of Corporate Ability. (June 2015) - Brammer, Stephen; He, Hongwei; Mellahi, Kamel
A growing body of research examines whether and how corporate social responsibility (CSR) leads to positive employee attitudes and work behaviors. While previous research suggests that CSR improves employee loyalty, motivation, satisfaction, and commitment, little research examines how CSR affects employee creativity. In addition, considerable skepticism remains regarding the significance of CSR in relation to employee attitudes and behaviors and of the potential contingencies that intervene in these relationships. In this study, we argue that the impact of CSR on employee creativity is contingent upon a focal firm's corporate ability (CA), that is, its expertise in producing and delivering its products/services. Specifically, we argue that CA not only influences employee organizational identification, hence employee creativity, but also affects how employees react to CSR. We test our arguments within a sample of professional workers in the telecommunication sector in Spain and find strong support for the proposed model.